The medical record as an instrument for monitoring off-label uses and drug related problem: the experience at the Mondovi Hospital. Issue 2 (12th March 2012) - Bagnasco, L.; Marengo, G.; Bramardi, A.; Bovetti, B.; Merlino, G.; Rosano, S.
Abstract : Background: The medical record is a document that accompanies the patient from his admission to the hospital. This document contains the objective examination, the patient's history, diagnostic activities practiced and therapy. Its compilation must be timely and must reflect the real situation. It is a valuable tool for testing and monitoring for use off label drugs in a hospital setting. Purpose: Since you use off label in a hospital is still virtually unknown. The hospital pharmacy, on the recommendation of the Health Department ASL CN1, began a sample monitoring of medical records of patients admitted to the hospital of Mondovi in the year 2010. Materials and methods: To quantify the problem of off-label prescriptions, which should be authorised by the Internal Pharmaceutical Care Commission, The authors have analysed medical records of the Internal Medicine, Hospital of Mondovi, who admits patients with multi-pathologies, often with complicated clinical situation and therefore represents a valid sample for an initial analysis. Results: During 2010 The authors have examined 50 medical records. This study showed that 36% of them have off label prescription drugs and the cases analysed are related to: Pantoprazole vials administered for longer than 15 min with a consequent loss of efficacy (15%); Antibiotics prescribed without an indication in antibiogram doing that can cause serious bacterial resistance (40%); Levoxacin administered in a dose of three times a day (5%); Tigecicline used at a dose of 100 mg for two days (5%); Fosfomicine not used for therapy of cystitis but for therapy of infection in immunocompromised (8%); Tramadol prescribed for chronic pain relief sublingual vials(10%); Rasburicase vials administered for longer than 30 min with a consequent loss of effectiveness (9%); Pantoprazole 40 mg tablets prescribed to prevent peptic ulcer discharge (8%). The analysis also revealed possible interactions between drugs (ex pantoprazole and iron gluconate with a probable decrease in the bioavailability of iron) and some dosage error (proton pump inhibitor with a full stomach, statins in of award administration and outside evening time, Bisoprolol in the treatment of heart failure with high doses once instead of a gradual increase, prednisone induction treatment with lower doses of 20-30 mg with possible ineffectiveness of therapy). Conclusions: The study clarifies that off-label prescriptions are still widely used in hospital practice. In addition to the purely regulatory issue the fundamental problem is health of patients, in fact use a drug outside the indication in the data sheet does not ensure safety, quality and efficacy guaranteed by registration studies. The figure of the clinical pharmacist to the bed of the patient during the therapy setting is crucial, as the guarantor of the appropriateness prescriptive.